2016
DOI: 10.1167/iovs.16-19153
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Treatment Limits Neuroinflammation in Experimental Glaucoma

Abstract: PurposeBesides primary neurotoxicity, oxidative stress may compromise the glial immune regulation and shift the immune homeostasis toward neurodegenerative inflammation in glaucoma. We tested this hypothesis through the analysis of neuroinflammatory and neurodegenerative outcomes in mouse glaucoma using two experimental paradigms of decreased or increased oxidative stress.MethodsThe first experimental paradigm tested the effects of Tempol, a multifunctional antioxidant, given through osmotic mini-pumps for dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
71
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(76 citation statements)
references
References 81 publications
(121 reference statements)
5
71
0
Order By: Relevance
“…Moreover, the accelerated glial activation in D2-ΔCS mice also correlated with an earlier induction of TNFα when compared to D2-WT mice. There is substantial evidence that TNFα is induced following elevated IOP (10, 12, 13, 53, 54,70) and is required for the death of RGCs (12, 13). Using the TNFα-induced model of glaucoma (12), we previously demonstrated that TNFα increased the expression of mFasL on retinal microglia and/or infiltrating macrophages and that Fas-FasL signaling was required for TNFα-mediated death of RGCs (28).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the accelerated glial activation in D2-ΔCS mice also correlated with an earlier induction of TNFα when compared to D2-WT mice. There is substantial evidence that TNFα is induced following elevated IOP (10, 12, 13, 53, 54,70) and is required for the death of RGCs (12, 13). Using the TNFα-induced model of glaucoma (12), we previously demonstrated that TNFα increased the expression of mFasL on retinal microglia and/or infiltrating macrophages and that Fas-FasL signaling was required for TNFα-mediated death of RGCs (28).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms involved in RGC death in glaucoma are complicated. The elevated intraocular pressure (IOP) is considered to be the major risk factor (Osborne, 2008; Ju et al, 2015; Yang et al, 2016), and lowering the IOP is thus far the only relatively effective treatment clinically (Chen et al, 2013; Itakura et al, 2015). However, lowering the IOP is not sufficient to prevent or delay progressive vision loss, and the molecular mechanisms underlying accelerated RGC loss, even when the raised IOP is lowered to a normal level for many years, remain poorly understood (Gupta and Yücel, 2007; Osborne, 2010).…”
mentioning
confidence: 99%
“…Moreover, antioxidant therapy has shown promising results in animal-and human-based research. Antioxidant treatment can decrease the activation of NF-κβ and decrease the production of cytokines in the optic nerve and retina [25]. In a rat glaucoma model, overexpression of thioredoxins can protect the RGCs [26].…”
Section: Discussionmentioning
confidence: 99%